Agricultural information videos to increase women's empowerment in agriculture in Uganda - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The intervention was rolled out in Eastern Uganda with 3500 farmers. Results are available in a report and a policy brief. The videos are publicly available.